IT'S OVER. - PHILLIPS, LISA A. (Psychology Today)
The article explores factors why some people find it harder to recuperate from broken relationships and ways for them to easily ease the pain. Topics discussed include previous researches on how people can quickly recoup from a nonmarital breakup, the role played by attachment-related anxiety in the recovery process and how being too dependent on a relationship can impact overcoming a romantic breakup.